Pelatihan Instalasi Listrik Rumah Tangga untuk Pemuda di Kecamatan Manggala Makassar sebagai Upaya Penciptaan Lapangan Kerja Baru - Yusran Yusran; Andani Ahmad; Indar Chaerah Gunadin; Muh. Bachtiar Nappu; Ardiaty Arief; Intan Sari Areni; Hasniaty A; Ida Rahmaniar Sahali; Andini Dani Achmad (Faculty of Engineering UNHAS, 2020)
The topic of community service activities is the Household Electrical Installation Training for Youth in Manggala District Makassar as an Effort to Create New Jobs. The method of activity is household electrical installation training with two approaches, theory and practice. The training was evaluated using the questionnaire method with closed questions. In general, the implementation of the training was considered to be going well. This is reflected in the responses of respondents in the training participant questionnaire Respondents who answered well were 28.6% and those who answered very well were 71.4%.